A comparison of neutrophil gelatinase-associated lipocalin and immature to total neutrophil ratio for diagnosing early-onset neonatal sepsis - Rocky Wilar; Dasril Daud; Suryani As’ad; Dwi Bahagia Febriani; Mina Mina (Indonesian Pediatric Society, 2016)
Background Neonatal sepsis is a clinical syndrome caused by the invasion of microorganisms into the bloodstream. Early diagnosis of early-onset neonatal sepsis (EONS) is difficult. Laboratory tests with high sensitivity and specificity are needed in order to make early diagnoses in newborns.Objective To compare the sensitivity and specificity of neutrophil gelatinase-associated lipocalin (NGAL) and immature to total (IT) neutrophil ratio for the diagnosis of early-onset neonatal sepsis.Methods This observational study with cross-sectional design was conducted in the Neonatology Division, Prof. R. D. Kandou General Hospital from November 2012 to April 2014. Consecutive sampling was applied. There were 103 newborns with suspected EONS who fulfilled the inclusion criteria. Complete blood counts, blood cultures, as well as NGAL and IT ratio measurements were performed.Results NGAL was not significantly more sensitive than IT ratio [80.4% vs. 67.3%, respectively; (P=0.058)]. However, NGAL had lower specificity than IT ratio (27.7% vs. 50.0%, respectively; P=0.016). The positive predictive values (57.0% vs. 64.9%, respectively; P=0.176), and negative predictive values (54.2% vs. 52.6%, respectively; P=0.451) were similar in both diagnostic tests.Conclusion Immature to total neutrophil (IT) ratio has higher specificity compared to NGAL for early diagnosis of EONS. However, the difference in sensitivity between the two test is not statistically significant.